2020
DOI: 10.1007/s10439-020-02534-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects on Fluid Mixing in the Eye

Abstract: Age-related macular degeneration (AMD) is the leading cause of central vision loss in the developed world. Wet AMD can be managed through serial intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents. However, sometimes the treatment is ineffective. Given that the half-life of the drug is limited, inefficient mixing of the injected drug in the vitreous chamber of the eye may contribute to the ineffectiveness. Here, we introduce thermal heating as a means of enhancing the mixing-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The role of naturally occurring thermal effects is expected to be minimal in terms of intravitreal drug transport. Very recent studies by Huang and Gharib [21] have shown experimentally that an imposed thermal stimulus on a fully liquid vitreous (experimental simulation model), buoyant convection can be significant. Also, Narasimhan and Sundarraj [22] investigated the thermal effects in a fully liquid vitreous.…”
Section: Hindrance Effectmentioning
confidence: 99%
“…The role of naturally occurring thermal effects is expected to be minimal in terms of intravitreal drug transport. Very recent studies by Huang and Gharib [21] have shown experimentally that an imposed thermal stimulus on a fully liquid vitreous (experimental simulation model), buoyant convection can be significant. Also, Narasimhan and Sundarraj [22] investigated the thermal effects in a fully liquid vitreous.…”
Section: Hindrance Effectmentioning
confidence: 99%